دراسة نظرية باستخدام DFT لبعض المركبات العضوية الكبريتية كمثبطات للتآكل - قرفي, حمزة; عزة, رحيمة (university of eloued جامعة الوادي, 2023)
في دراستنا النظرية هذه قمنا بتحليل ثلاث مركبات كيميائية وهي : Ethanethioamide ، Thiourea ، Benzothioamide و هي عبارة عن مثبطات عضوية مضادة للتآكل ، و تتميز هذه المركبات بأن لها نفس النواة الأساسية في بنيتها مكونة من ذرات ) 2HN-C=S ( ، حيث استخدمنا في دراستنا النظرية عدة برامج أهمها برنامج الحساب Gaussian09 بطريقة نظرية الكثافة الوظيفية DFT بقاعدة B3LYP / 6 - 311G . الهدف الأول من دراستنا هو دراسة الترابط بين الفعالية التثبيطية التجريبية للمركبات المدروسة و البنى الجزيئية ، و لقد وجدنا ت وافق بحيث أن المثبط الثالث benzothioamide هو الأفضل ، من خلال عدة معايير أهمها امتلاكه لأقل فرق طاقوي ( Egap=4.0300972 ( كوذلك أكبر عدد للالكترونات المنتقلة ) NΔ ( ، وكذلك أكبر طاقة تجاذب مثبط معدن ) ΔΨ ( و أكبر طاقة متبادلة ) D-BE . ) الهدف الثاني من دراستنا هو تحديد آلية الامتزاز الكيميائي من خلال دراسة قيم شحن ميليكان ، خرائط الكم ون الكهروستاتيكي ، قيم مساهمات أربيتالات مدار HOMO ، مؤشر fukui . التي مكنتنا من تحديد الموقع النكليوفيلي ) الكبريت S ( و الالكتروفيلي ) الكربون C2 . ) الIn our theoretical study, we analyze three chemical compounds: ethanethioamide, thiourea, and benzothioamide , which are organic anti-corrosion inhibitors. The( S=C-NH2 ) group is the common main group for these compounds and they differ only having different groups on the other side of the thiocarbonyl group . in our study , we used several programs, the most important of which is the Gaussian09 calculation program using the DFT method based on B3LYP/6-311G. The primary objective was to examine the correlation between the inhibitory activity of the compounds under investigation and their molecular structures. we concluded that the third inhibitor, (benzothioamide) is the most effective compound based on several criteria, with the most significant factors being the least energy difference (Egap), the largest number of transferred electrons (ΔN), the largest inhibitory-metal attraction energy (ΔΨ), and the largest exchange energy ( EB-D ( . The second objective of our study is to investigate the mechanism of chemisorption reactions by analyzing various parameters such as Millikan charge values, electrostatic potential maps, HOMO orbital contributions values, and Fukui indices. These analyses allow you to make determination about the nucleophile site (sulfur S) and electrophilic site (carbon C2) .
مذكرة ماستر كيمياء
Keywords: كلمات المفتاحية : التآكل ، مثبطات التآكل ، الامتزاز ، HOMO ، LUMO ، DFT .; corrosion, corrosion inhibitors , adsorption , HOMO, LUMO, DFT.